Liquidity And Performance: Evidence From Actively Managed Open Ended Equity Funds Of Msci- Asian Emerging Countries - Kumar, Suresh (2023)
First, this study looks for an additional expected return from illiquid funds (the least liquid funds) over liquid funds (the most liquid funds), called the liquidity premium. Second, using regression analysis, funds can be classified as sensitive funds (high liquidity beta funds) or insensitive funds (low liquidity beta funds) to shocks in market liquidity in order to approach the liquidity risk premium